Mitral annulus dynamics in myxomatous mitral valve disease - Maria-Magdalena Gurzun; Monica Rosca; Andreea Calin; Carmen Beladan; Marinela Serban; Roxana Enache; Ruxandra Jurcut; Carmen Ginghina; Bogdan A. Popescu (Romanian Journal of Cardiology, 2021)
Myxomatous mitral valve disease (MVD) is a common disorder in which the entire mitral valve apparatus seems to be involved. Mitral valve repair is nowadays the method of choice for the correction of mitral regurgitation but the optimal shape and flexibility of the annuloplasty ring remain controversial. Considering that myxomatous MVD covers a wide spectrum from limited fi bro-elastic deficiency to extensive Barlow disease, we presume that the mitral annulus morphological and functional changes are likely different in different types of myxomatous MVD. We analyze the 3-dimensional geometry and the dynamics of the mitral annulus in 110 patients with significant mitral regurgitation due to different types of myxomatous mitral valve disease and 40 normal subjects using 3D transesophageal echocardiography. The mitral annulus differs in patients with limited MVD, extensive MVD and in normal controls in terms of size, shape, and dynamics. Patients with limited MVD have larger, flatter, dysfunctional and more mobile mitral annulus compared to normal, while patients with extensive MVD have even larger, flatter and more dysfunctional mitral annulus, with reduced mobility. The non-planar dynamics has different patterns during systole, according to the extension of MV disease. Our data may be important for the appropriate choose of annuloplasty mitral annulus in mitral valve repair, the current trend being to choose the ring according to the underlying pathology.